2001
DOI: 10.1038/sj.ejcn.1601146
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient and food intake in the Baltic republics

Abstract: Objective: The objective of this study was to describe mean macronutrient and food intakes in the Baltic republics, with a particular focus on fat, vegetable and fruit consumption. Design: Cross-sectional study. Setting: Data from surveys conducted in Estonia, Latvia and Lithuania in the summer of 1997 were used. Information was collected using a 24 h recall of dietary intake and an interviewer-administered questionnaire. Subjects: Representative national samples of adults were selected. All those with informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…Republics (Pomerleau et al, 2001) and Italy (Turrini et al, 2001) have not quantified variation in the evaluation in intakes among recognized determinants, although they are to some extent considered by calculating simple averages and=or medians. However, some studies have compared differences in crude mean values with or without standard errors at different points in time, supplemented with estimates from food supply data in order to evaluate trends (Dobson et al, 1997;Harnack et al, 2000;Kim et al, 2000).…”
Section: Food Consumption In Rural Bangladeshmentioning
confidence: 99%
“…Republics (Pomerleau et al, 2001) and Italy (Turrini et al, 2001) have not quantified variation in the evaluation in intakes among recognized determinants, although they are to some extent considered by calculating simple averages and=or medians. However, some studies have compared differences in crude mean values with or without standard errors at different points in time, supplemented with estimates from food supply data in order to evaluate trends (Dobson et al, 1997;Harnack et al, 2000;Kim et al, 2000).…”
Section: Food Consumption In Rural Bangladeshmentioning
confidence: 99%
“…From the sourced articles, fifty-one pan-European studies in total were identified: thirty-five named projects and sixteen smaller projects (48,54,56,65,69,72,82,83,88,93,94,107,109,113,114,116) . Most studies assessed dietary intake of F&V among adults (18,41,44,46,48,50,51,(54)(55)(56)(57)59,60,(64)(65)(66)68,69,71,72,(75)(76)(77)(78)(79)(81)(82)(83)(84)86,88,(92)(93)(94)107,…”
Section: Public Health Nutritionmentioning
confidence: 99%
“…2 (Italy, Spain) FFQ X (53) Baltic project (55) 3 (Latvia, Lithuania, Estonia) 24-HDR Standardised questionnaire Behanova et al (56) 2 (Slovakia, Netherlands) FFQ CNSHS (57,58) 4 (Germany, Denmark, Poland, Bulgaria) FFQ X ECRHS (59) 3 (Germany, UK, Norway) FFQ (based on EPIC-UK and EPIC-Germany FFQ) X (59) EHBS (60) 21 in total FFQ X 17 European countries (Austria, Denmark, England, Finland, France, Germany, Greece, Iceland, Ireland, Netherlands, Norway, Poland, Portugal, Scotland, Spain, Sweden, Switzerland) ENERGY (27) 7 (Belgium, Greece, Hungary, Netherlands, Norway, Slovenia, Spain) FFQ X (28) X EPIC (18,28,29,61,62) 10 (Italy, Spain, Netherlands, Germany, Sweden, Denmark, France, Greece, Norway, England)…”
Section: Public Health Nutritionmentioning
confidence: 99%
“…The discrepancies between databases observed for fat intakes are particularly important. Although this may not be of importance to track changes in fat intake over time within one country, it requires us to reconsider the results of the Baltic Nutrition Surveys (Pomerleau et al, 2001), which suggested a lower fat intake in Estonia (37% of dietary energy in male subjects and 36% in female subjects) compared with Latvia (43% in male subjects and 41% in female subjects) and Lithuania (45% in male subjects and 43% in female subjects). Indeed, we can postulate that this difference may be partly due to differences between the food composition databases used to convert survey information into nutrients, and not to true differences in intakes.…”
Section: Comparison Of the Food Composition Databases S Vaask Et Almentioning
confidence: 99%
“…As two different databases were used to derive nutrient intakes in the Baltic Nutrition Surveys, this study set out to investigate whether intrinsic differences between the Russian and adapted-Finnish databases could have influenced between-country variations in estimated nutrient intakes (Pomerleau et al, 2001). The objective of the study was to compare the databases at two different levels: first the energy and nutrient composition of 15 foodstuffs commonly consumed by the populations of the region (Kasmel et al, 1998), and second the mean energy and nutrient intake of a sample of 32 survey participants.…”
Section: Introductionmentioning
confidence: 99%